AB0663 Efficacy and Safety of Adalimumab in Patients with Axial Spondyloarthritis - An Investigator-Initiated Randomized Placebo-Controlled Trial. (15th July 2016) - Krabbe, S.; Østergaard, M.; Sørensen, I.J.; Jensen, B.; Madsen, O.R.; Eng, G.P.; Asmussen, K.H.; Møller, J.; Balding, L.; Pedersen, S.J.
Abstract : Background: This study investigates the effect of adalimumab (ADA) in patients with axial spondyloarthritis (axSpA). Objectives: In an investigator-initiated randomized, placebo-controlled, double-blinded trial (NCT01029847 ) the efficacy of adalimumab was investigated in patients with axSpA according to the Assessment of Spondyloarthritis International Society (ASAS) criteria.(1, 2) Methods: 49 patients with axSpA, BASDAI≥4.0 despite treatment with NSAID and clinical indication for TNFα inhibitor treatment were randomized to s.c. placebo (PLA) or ADA 40 mg eow from baseline to week 6. All patients received ADA from weeks 6 to 24. At week 24, patients with a BASDAI reduction >50% or 2.0 were considered responders. MRI of the spine was scored according to SPARCC Spine Inflammation Index by an experienced reader blinded to all other data. Data from the randomized period (week 0–6) were analysed by Chi-square, unpaired t-tests and Mann-Whitney U tests as appropriate. Results: Mean (range) age was 38 years (20–61), symptom duration 12 years (0–45) and time since diagnosis 3 years (0–38). 51% were males, 74% HLA-B27 positive, 20% had a history of uveitis, 4% of psoriasis and 6% of inflammatory bowel disease. At week 24, a BASDAI reduction >50% or 2.0 was attained by 32 of 49 (65%) patients (58% and 72% in the PLA and ADA groups, respectively). 61% of patients achieved ASAS 20 response and 61% ASAS 40 response. From baseline to week 6, the SPARCC MRI spine score improved significantly more in the ADA group than in the PLA group, as did clinical variables (Table): Treatment was discontinued in 5 patients due to adverse events during ADA treatment, due to rash (1), unspecified allergic reaction (1), paresthesia and reduced sensibility of 2 fingers (1), back pain worsening (1), and hospitalization due to myalgia and malaise (1). Conclusions: Adalimumab significantly improved clinical and MRI measures of disease activity already at week 6 compared to placebo. 2/3 of patients achieved the clinical endpoint at week 24, confirming the clinical efficacy in axSpA. References: Maxwell et al. Cochrane Database Syst Rev. 2015;4:CD005468. Rudwaleit et al. Ann Rheum Dis 2009;68:777–83 Disclosure of Interest: None declared